2017
DOI: 10.1016/j.foodchem.2016.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification properties of polysaccharides from Dioscorea opposita Thunb.

Abstract: This study investigated the emulsification properties of polysaccharides from Dioscorea opposita Thunb. Graded alcohol precipitation was used to extract Dioscorea opposita polysaccharides fractions (4 samples) in different ranges of molecular weight. Sample 3 contained more glucose and protein (80.13% and 0.34%, respectively), and molecular weight was approximately 34,790Da, distributing narrowly. The droplet sizes and stabilities of emulsions made of gum arabic (GA) and polysaccharide samples at different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…The particle sizes of both AOP and F-AOP solutions were concentration-dependently increased. The droplet sizes of polysaccharide solutions generally increased with the increased concentrations . Here, the average particle size of F-AOP solution at 20 mg/mL were comparable to that of AOP solution at 5 mg/mL, indicating a considerable and significant difference in Zp values between F-AOP and AOP.…”
Section: Results and Discussionmentioning
confidence: 74%
“…The particle sizes of both AOP and F-AOP solutions were concentration-dependently increased. The droplet sizes of polysaccharide solutions generally increased with the increased concentrations . Here, the average particle size of F-AOP solution at 20 mg/mL were comparable to that of AOP solution at 5 mg/mL, indicating a considerable and significant difference in Zp values between F-AOP and AOP.…”
Section: Results and Discussionmentioning
confidence: 74%
“…In addition, subsequent reports indicated that DOP had a modulating effect on the improvement in glucose metabolism and insulin sensitivity in rats receiving a high-fructose diet by reducing inflammatory protein products (including levels of IL-1β, TNF-Îą) and increasing the levels of antioxidant enzyme (SOD) activity [ 23 , 24 , 25 ]. Moreover, DOP was also expected to serve as a natural thickener and emulsifier in the food industry due to its good “gel-like” behavior and emulsification properties [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine believes it has multiple nutritional and medicinal values such as nourishing liquid and lung, reinforcing the kidney, controlling nocturnal emissions and invigorating QI and YIN [2,3]. Yam polysaccharides are considered to be the main active components, including homopolysaccharides, heteropolysaccharides and glycoproteins, and its molecular weight ranges from thousands to tens of millions [4]. Existing studies have shown that yam polysaccharides possess a variety of biological activities, including anti-oxidation [5], immunomodulation [6,7], hypoglycemia [8] and regulating the intestinal flora [9,10].…”
Section: Introductionmentioning
confidence: 99%